Legal Development of the Malaysian Consumer Protection Act 1999: 20 Years After - Roshazlizawati Mohd Nor, Nor Zafir Md Salleh, Zuraidah Sulaiman, Siti Zaleha Omain, Mohd Noor Azli Ali Khan, Ungku Norulkamar Ungku Ahmad (International Journal of Advanced Science and Technology, 2020)
Consumer Protection Act (CPA) 1999 was enforced in Malaysia on 15 November 1999 after it was reviewed for almost six years and finally tabled before the Parliament in 1999. There are 14 parts and 150 sections in CPA 1999 that protects the consumers through the National Consumer Advisory Council (NCAC) and Tribunal for Consumer Claims (TCC). Focusing on CPA as the primary legislation that incorporates provisions to adequately protect the consumers, its legal development and effectiveness in improving the position of consumers in Malaysia for the past two decades were reviewed in this paper. As a doctrinal study, content analysis was employed to explore the development and effectiveness of TCC in serving its core function as well as the impact of CPA amendments on the protection of consumer rights. The findings of this study were deemed significant for the future development of CPA in protecting consumer rights and gaining public confidence Index Terms: Amendment of law, Consumer Protection Act 1999, legal development, Tribunal for Consumer Claims